A benchmark concentration-based strategy for evaluating the combined effects of genotoxic compounds in TK6 cells - George Johnson (Archives of Toxicology, 2025)
Chemical risk assessment has historically focused on single compounds, neglecting the implications of combined exposures. To bridge this gap, several methodologies, such as concentration addition (CA) and independent action (IA), have been developed. However, a systematic, consistent, and integrated approach across various legislative frameworks is still lacking. The assessment of combined effects of genotoxicants is even more challenging, as genotoxicity data are typically evaluated qualitatively, without considering the effect size. This study aimed to develop a quantitative approach for evaluating the combined effects of genotoxic compounds with both similar and dissimilar modes of action (MoA), based on the benchmark concentration (BMC) principle. A proof-of-concept study was conducted using the in vitro micronucleus (MNvit) test to examine two types of binary mixtures: ethyl methanesulfonate (EMS) and methyl methanesulfonate (MMS), which share similar MoA, and MMS and etoposide (ETP), which have dissimilar MoA. The methodology involved collecting data for individual compounds, calculating BMC values, composing mixtures with different ratios and inducing various effect levels, testing these mixtures, and comparing the experimental results with the modelled data to verify additivity. The findings indicated that for both mixtures, the experimental responses aligned with the predicted additive effects, supporting the validity of the additivity principle. This study highlights the potential of an optimized BMC-based approach as a robust framework for testing chemical mixtures. It should be adopted in future studies to evaluate a wider range of genotoxic compounds, offering a more comprehensive and quantitative strategy for assessing combined chemical exposures.